Digital Business Models in the Industry 4.0 Era: A Bibliometric Lens on Evolutionary Trends and Scholarly Trajectories - Usada, Saskia; Rico Erlangga; Rafli Aly Yahya; Nashyifa Kayla; Muhammad Ramadhani Kesuma (INDO PUBLISHING, 2026)
The rapid advancement of Industry 4.0, driven by cyber-physical systems, IoT, AI, cloud computing, and big data analytics, has reshaped contemporary business landscapes. Digital Business Models (DBMs), characterized by scalability, platform-based value creation, and collaborative, data-driven processes, are critical enablers of this transformation. However, the growing body of DBM research lacks coherence and a unified conceptual framework within the context of technological evolution. This study adopts a bibliometric approach to systematically map the intellectual and thematic landscape of DBM research related to Industry 4.0 between 2019 and 2025. Using performance analysis and science mapping methods with VOSviewer, publication trends, thematic clusters, and collaboration networks were identified. Results reveal a shift from single-technology focus to multi-dimensional themes including platformization, value co-creation, digital transformation strategies, and ecosystem orchestration. Germany and Austria emerge as leading contributors in global research collaboration. This study contributes theoretically by defining the intellectual structure of the DBM field and identifying frontier topics. Practically, it offers actionable insights for enterprises deploying agile, technology-enabled DBMs under dynamic competitive environments and guides future research agendas in this rapidly evolving domain.